EFFECT OF SOLID AND LIQUID ORGANIC FERTILIZER ON GROWTH, YIELD AND YIELD COMPONENTS OF ROSSELLE (Hibiscus sabdariffa L.) IN THE NIGERIAN SAVANNAH - Ladan, K. M.; Abubakar, M. G.; Suleiman, J. (FUDMA JOURNAL OF SCIENCES, 2021)
The Study was conducted to evaluate the effect of solid and liquid organic fertilizer on growth and yield of rosselle in 2016 cropping season at Institute of Agricultural Reserve Zaria, Samaru (11011â€™N 07038E and 686m) and Institute of Horticultural Research Farm Bagauda (12000â€™N 8031â€Em 488m) in Northern Guinea Savannah and Sudan Savannah Ecological Zones of above sea level Nigeria. Treatments consisted of four levels of solid poultry manure (0.0, 1.0, 2.0 and 3.0) tons/ha and five levels of liquid organic manure from Grand Total Organic Fertilizer Limited (0.0, 0.5, 1.0, 1.5 and 2.9) litres/ha, which were factorially combined in a randomized complete block design (RCBD) and replicated three times. Data on growth parameter were collected on plant height (cm), plant dry weight (g), leaf Area index crop growth rate (CGR) Relative Growth Rate (RGR) and Net assimilation rate (NAR) while data on yield parameters like number of calyx per pant, 100 seed weight (g) and  calyx yield per hectare kg/ha were collected. Results showed that plant height, plant dry weight(g), 100 seed weight(g) and calyx dry yield kg/ha had a significant increase with application of 2.0 litres/ha of liquid fertilizer than other rates. While application of solid poultry manure at 3.0ton/ha significantly increases plant height, net assimilation rate, leaf area index and calyx dry weight when compared with other rates. From the results obtained, the combination of 2.0 litres/ha liquid organic fertilizer and 3.0 ton/ha solid poultry manure produce the highest calyx yield at both location.
Keywords: Rosselle, solid, liquid, organic fertilizer growth, yield and Nigerian Savannah